Menstrual Cycle of Adolescent Girls Aged 15-18 Years in SMAN 74 Jakarta: The Effect of Vitamin and Mineral Intakes and Physical Activity - Winarno, Putri Sopya Nita; Putri, Imawati Eka; Ningtyas, Luthfiana Nurkusuma (Universitas Muhammadiyah Surakarta, 2022)
Purpose: This study aims to determine the relationship between the intake of vitamins (vitamin C and vitamin D), minerals (iron and calcium), and physical activity with the menstrual cycle in adolescent girls at SMAN 74 Jakarta. Methodology: The population used was all adolescent girls and a sample of 87 adolescent girls at SMAN 74 was obtaines. The study design use cross-sectional with a purposive sampling technique. The SQFFQ using interviews is used to get data on vitamin and mineral intake, a questionnaire is used to get the data on the menstruation cycle, the IPAQ using interviews is used to get the data on physical activity among women student in SMAN74 Jakarta. Statistical analysis using chi-square with a significant level of 5% (vitamin C, iron, and physical activity) and fisher exact (vitamin D and calcium).Results: The results of this study found menstrual cycle irregularity is still high adolescent girls, adequate vitamin C intake, insufficient intake of vitamin D, iron, calcium, and heavy physical activity in adolescent girls. This study that states there is a significant relationship between iron intake and the menstrual cycle, while intake of vitamin C, vitamin D, calcium, and physical activity there is no relationship.Applications/Originality/Value: This study that states there is a significant relationship between iron intake and the menstrual cycle. For adolescent girls, they should increase their intake of nutritional sources, especially iron so that they pay more attention to the menstrual cycle they experience for reproductive health.